The Influence of Time on Artworks: A Hermeneutical Reading of Holocaust Films - Abdullah Başaran (İnsan & Toplum)
This article’s aim is to focus on the close relationship that exists between the notions of prejudice and historicity and the time in which a film director of genocide lives and the extent to which their temporality unavoidably colors their artistic response to a historical event, such as the Holocaust. In this regard, depending on such an event, a categorization of people will be offered: victims and survivors, survivors’ children who born after genocide, witnesses of victims and survivors, and, finally, people born after the genocide. In this way, according to the main argument of this essay, the time period the film director lives in relative to the event is one of the criteria for evaluating their artwork in virtue of the formation of their prejudices and of their approach to the Holocaust as a historical event. But it must be noted that this essay will not argue that films of the directors belonging to any of the particular categories are better representations of the Holocaust than the films of the others. Instead, it will be stated that there appears a two-stage linguistic gap among human beings when directors narrate their own experience or highlight the significance of the event per se.